2019
DOI: 10.1002/cam4.2222
|View full text |Cite
|
Sign up to set email alerts
|

Survival and clinical prognostic factors in metastatic non‐clear cell renal cell carcinoma treated with targeted therapy: A multi‐institutional, retrospective study using the Korean metastatic renal cell carcinoma registry

Abstract: Objectives The optimal treatment strategy for metastatic non‐clear cell renal cell carcinoma (mNCCRCC) is still elusive and mainly extrapolated from evidence available for metastatic clear cell renal cell carcinoma. The aim of the study was therefore to investigate the survival outcomes and prognostic factors affecting survival in patients with mNCCRCC treated with targeted therapy. Materials and methods We analyzed a total of 156 patients (8.1%) with mNCCRCC among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
1
16
1
Order By: Relevance
“…Data of the 4,246 enrolled patients with RCC were obtained from two multicenter RCC databases—the nmRCC ( 8 ) and mRCC ( 9 ) databases—that were obtained from the Multicenter Korean National Kidney Cancer (MKNKC) database. A total of 464 (10.9%) patients with RCC were selected for this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data of the 4,246 enrolled patients with RCC were obtained from two multicenter RCC databases—the nmRCC ( 8 ) and mRCC ( 9 ) databases—that were obtained from the Multicenter Korean National Kidney Cancer (MKNKC) database. A total of 464 (10.9%) patients with RCC were selected for this study.…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective study was approved by the institutional review board of the National Cancer Center (approval number: NCC 2018-0045 and B1202/145-102), which waived the requirement for informed consent due to the retrospective nature of this study (8)(9)(10). All study procedures were performed in accordance with the tenets of the ethical guidelines and regulations of the Ethical Principles for Medical Research Involving Human Subjects of the World Medical Association Declaration of Helsinki.…”
Section: Ethical Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Dragomir et al conducted a 1:4 PSM analysis of 229 MTX patients and found that the median OS was significantly different compared to the matched group (81 months (interquartile range [IQR] 58 -Not reached (NR)) vs. 61 months (IQR 26 -NR; p = 0.0001), respectively (21). Similarly, MTX was also associated with improved cancer-specific mortality (CSM) and PFS (24,28,32,38,41,42). A large study by Wu et al in 2020 utilizing data from 2,911 mRCC patients found that MTX was significantly associated with decreased CSM (3-year cumulative incidence 52.6 vs. 59.2%, Hazard Ratio (HR) 0.875, 95% Confidence Interval (CI) 0.773-0.991; p = 0.015) (24).…”
Section: Metastasectomy Status and Clinical Outcomesmentioning
confidence: 99%
“…In addition, a recent retrospective study, although involving only Asian patients (16), confirmed that the survival outcomes for the metastatic non clear cell RCC cohort were significantly inferior to the outcomes for the metastatic clear cell RCC cohort regarding to first-line PFS, total PFS, and cancer specific survival (CSS), except for the chromophobe and Xp 11.2 translocation groups that showed better survival outcomes compared to clear cell RCC. Contrariwise, first line PFS, total PFS and CSS for the other histologies evaluated in this study (like the collecting duct, papillary, and unclassified groups) were meaningfully poorer compared to those of the group clear cell RCC.…”
mentioning
confidence: 97%